Kontribusi Tenaga Kerja Wanita Pada Usaha Home Industry Emping Melinjo Terhadap Pendapatan Keluarga Di Desa Tebing Tanjung Selamat, Kabupaten Langkat - Laili Azueni Vicesta; Fiddini Alham; Rozalina Rozalina (Jurnal Penelitian Agrisamudra, 2021)
This study was conducted with the aim of analyzing the income of women workers in the melinjo chips home industry business in increasing family income and analyzing the contribution of the income of women workers in the melinjo chips home industry business to family income in Tebing Tanjung Selamat Village, Padang Tualang District, Langkat Regency. The location of this research was carried out in Tebing Tanjung Selamat Village, Padang Tualang District, Langkat Regency with the consideration that the area is a home industry for melinjo chips. Primary data was obtained by means of direct interviews and questionnaires with respondents. In this study, the number of samples was 21 female workers who worked in the melinjo emping home industry who were married. The determination of the number of samples used by the author in this study is the saturated sample method. The data analysis used is descriptive quantitative and qualitative for the involvement of women workers in the melinjo emping home industry business and the contribution of income obtained from women workers. The results showed that; 1) The average income earned by female workers every month is Rp. 655.429/Month. This income is far below the UMK (Regency/City Minimum Wage) of Langkat Regency, which is Rp. 2,711,000. However, this income is considered very helpful for the family's economy. 2) The contribution of female workers' income to family income is 26%, meaning that the contribution of female workers' income based on the contribution interval scale is included in the medium contribution criteria (20.00-30.00%).